Influence of storage environment on maize grain: CO2 production, dry matter losses and aflatoxins contamination - Garcia-Cela, Esther; Kiaitsi, Elisavet; Sulyok, M.; Krska, R.; Medina-Vayá, Ángel; Petit Damico, I.; Magan, Naresh (Food Additives & Contaminants: Part A, 2019)
Poor storage of cereals, such as maize can lead to both nutritional losses and mycotoxin contamination. The aim of this study was to examine the respiration of maize either naturally contaminated or inoculated with Aspergillus flavus to examine whether this might be an early and sensitive indicator of aflatoxin (AF) contamination and relative storability risk. We thus examined the relationship between different interacting storage environmental conditions (0.80–0.99 water activity (aw) and 15–35°C) in naturally contaminated and irradiated maize grain + A. flavus on relative respiration rates (R), dry matter losses (DMLs) and aflatoxin B1 and B2 (AFB1-B2) contamination. Temporal respiration and total CO2 production were analysed by GC-TCD, and results used to calculate the DMLs due to colonisation. AFs contamination was quantified at the end of the storage period by HPLC MS/MS. The highest respiration rates occurred at 0.95 aw and 30–35°C representing between 0.5% and 18% DMLs. Optimum AFs contamination was at the same aw at 30°C. Highest AFs contamination occurred in maize colonised only by A. flavus. A significant positive correlation between % DMLs and AFB1 contamination was obtained (r = 0.866, p < 0.001) in the irradiated maize treatments inoculated with A. flavus. In naturally contaminated maize + A. flavus inoculum loss of only 0.56% DML resulted in AFB1 contamination levels exceeding the EU legislative limits for food. This suggests that there is a very low threshold tolerance during storage of maize to minimise AFB1 contamination. This data can be used to develop models that can be effectively used in enhancing management for storage of maize to minimise risks of mycotoxin contamination.